Pengaruh Usia dan Masa Kerja Terhadap Produktivitas Kerja (Studi Kasus: PT. OASIS Water International Cabang Palembang) - Selvia Aprilyanti (Universitas Serang Raya, 2017)
Age and years of service are factors directly related to work productivity. Age and employment perceived by employees can decrease productivity or increase employee productivity. This research was conducted at PT. Oasis Water International Palembang Branch and aims to determine the influence of Age and Duration of employment on employee productivity. The number of sample is 27 respondents by using random sampling technique. Analysis method used is multiple linear regression method using SPSS aid which includes t test and F test. As independent variable (independent), that is age and work period, while dependent variable is work productivity. The result of data analysis showed that the variable of age and duration of work did not have a positive effect on work productivity, where the probability value of F test of significance value for the effect of age and work period simultaneously to productivity was 0.355 > 0.05 and F value count 1.083 <F table 3.39, and from the results of the analysis using the coefficient of determination known that the factor of age and employment only has an effect of 8.3 percent (%) on work productivity in the company PT.Oasis Water International.